Phages Bind to Vegetative and Spore Forms of Paenibacillus larvae and to Vegetative Brevibacillus laterosporus - Brady, T. Scott; Roll, Charles R.; Walker, Jamison K.; Fajardo, Christopher P.; Breakwell, Donald P.; Eggett, Dennis L.; Hope, Sandra (Frontiers in Microbiology, 2021)
Paenibacillus larvae is the causative agent of American Foulbrood (AFB), the most destructive bacterial infection in honeybees. Even antibiotic-sensitive strains of P. larvae can produce recurrent AFB months to weeks post-antibiotic treatment due to the survival of bacterial spores. Recently, phages that infect P. larvae have been shown to effectively combat AFB in the field. Here, we present evidence that phages not only bind to vegetative P. larvae but also bind to P. larvae spores. Spore binding was observed in the results of three specific experiments: (1) bacteria counted by flow cytometry generated quantitative data of FITC-labeled phages that were bound to vegetative bacteria as well as those bound to spores, (2) electron microscopy captured images of phages bound to the surface of spores in both horizontal and vertical positions, and (3) phages incubated with P. larvae spores bound to the spores and created plaques in vegetative bacteria under conditions not conducive to spore activation, indicating that binding to spores is reversible and that the phages are still active. Identification of phages with reversible spore-binding capability for use in phage therapy may improve treatment of sporulating bacterial infections.